UNIVERSITAS INDONESIA’S SCIENCE AND TECHNOLOGY (IPTEK) GLOBAL PARTNERSHIP IMPACT TOWARDS THE SUSTAINABILITY OF INDONESIA’S KNOWLEDGE-BASED ECONOMY THROUGH MODERATING VARIABLES - Akbar, Maruf; Matin, Matin; Sari, Rini (UI Scholars Hub, 2022)
Global Innovation, science and technology performance is one of the essential problems that Indonesian universities face. Currently, sciences and technology (IPTEK)’s partnership among university, government, industry, and Indonesia’s society have not been conducted optimally. This paper discusses the impact of the relationship between university’s science and technology global partnership, QS/world university ranking, university/industry research collaboration with sustainability knowledge-based economy (KBE) as well as suggesting some possible solutions for optimization. The investigation was followed by a cause-and-effect analysis that was gained from several secondary data and reports such as Global innovation Index (GII), UI Scholar, QS, THE, SINTA, ASEAN Benchmarking’s data during 2010 to 2020. These are gathered to calculate and analyse the correlation-determination (r & Kd), significance test (t-count and t-table), and moderating variables (MRA). Analysis data uses descriptive statistics and a simple regression technique. The results showed that QS university ranking and university/industry research collaboration as a moderating relationship of UI’s IPTEK global partnership have a simultaneously positive and significant effect on the sustainability of Indonesia's knowledge-based economy. Three of six hypotheses have showed very significant results, with numbers roughly above 85% up to 98%, H2: 88.5%, H3: 89.6%, 98.6% MRA of X2 against X3 respectively. In comparison with the two others, several are above 60%. These are X1 against X3:74.5% and X1 to X4: 67.5% respectively. The remaining one is X1 against X2: 25.7%, which examines the direct effects between independent and dependent variables without using the moderating variables. Hence, it is argued that contributions of a higher education institution to sustainability KBE could be determined by the level of their competitiveness on regional and global levels. This study may serve as motivation for universities particularly in Indonesia to strive with their existing resource capacities continuously. Hence, UI could serve as a role model to the other universities in Indonesia.